2005
DOI: 10.1128/aac.49.10.4042-4045.2005
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacies of Quinupristin-Dalfopristin, Linezolid, Vancomycin, and Ciprofloxacin in Treatment, Using the Antibiotic-Lock Technique, of Experimental Catheter-Related Infection Due to Staphylococcus aureus

Abstract: We performed in vitro studies to elucidate the bactericidal activity of the antibiotics in an adherent-cell biofilm model. Efficacy studies were performed in a staphylococcal central venous catheter (CVC) infection rat model. Silastic catheters were implanted into the superior cava. Via the CVC the rats were challenged with 1.0 ؋ 10 6 CFU of a live Staphylococcus aureus strain. Twenty-four hours later, the antibiotic-lock technique was started. All animals were randomized to receive daily isotonic sodium chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 21 publications
5
28
0
Order By: Relevance
“…aureus polymicrobial biofilms. Interestingly, while we observed that a high concentration of ciprofloxacin (1024 mg/L) failed to eliminate a mature S. aureus ATCC 25923 biofilm, in accordance with previously published studies, 35,44,45 a much lower concentration of ciprofloxacin (4 mg/L) used in combination with antifungal agents was effective against the same bacterium grown in a polymicrobial biofilm with C. albicans, causing a 99.6% reduction in viable cell counts. The difference in ciprofloxacin effectiveness against monomicrobial and polymicrobial biofilms might be due to differences in the biofilm structure, cell physiology or extracellular matrix composition between single bacterial and mixed fungal/bacterial biofilms.…”
Section: Discussionsupporting
confidence: 76%
“…aureus polymicrobial biofilms. Interestingly, while we observed that a high concentration of ciprofloxacin (1024 mg/L) failed to eliminate a mature S. aureus ATCC 25923 biofilm, in accordance with previously published studies, 35,44,45 a much lower concentration of ciprofloxacin (4 mg/L) used in combination with antifungal agents was effective against the same bacterium grown in a polymicrobial biofilm with C. albicans, causing a 99.6% reduction in viable cell counts. The difference in ciprofloxacin effectiveness against monomicrobial and polymicrobial biofilms might be due to differences in the biofilm structure, cell physiology or extracellular matrix composition between single bacterial and mixed fungal/bacterial biofilms.…”
Section: Discussionsupporting
confidence: 76%
“…While some previous in vitro studies have shown the effectiveness of antibiotics, such as vancomycin, daptomycin, and rifampin, as ALTs (7,8,19,23), others have demonstrated the opposite effect, as well as the ineffectiveness of other antibiotics, such as linezolid, gentamicin, and oxacillin (12,24,25). In our study, the antibiotics daptomycin, vancomycin, tigecycline, and rifampin resulted in a significant reduction in the viability of S. aureus biofilms formed over a 24-h incubation period.…”
Section: Discussionmentioning
confidence: 60%
“…Heparin alone was completely ineffective, and heparin in combination with either ciprofloxacin or vancomycin did not improve efficacy. A study by Giacometti et al (2005) found that neither vancomycin nor ciprofloxacin were highly effective against catheterassociated biofilms of S. aureus in a rat model, though quinupristin-dalfopristin provided a 4-log biofilm plate count reduction compared to the untreated control under the same conditions. These results are not encouraging since none of the agents evaluated in these studies were capable of eradicating biofilms on implanted devices.…”
Section: Animal Model Studiesmentioning
confidence: 94%
“…Linezolid is an oxazolidinone that inhibits protein synthesis of most Gram-positive bacteria, including strains that are resistant to the b-lactams and glycopeptides (Shinabarger et al 1997). Others have demonstrated the efficacy of linezolid (El-Azizi et al 2005;Giacometti et al 2005), rifampin (a RNA polymerase inhibitor) (Monzon et al 2002;Peck et al 2003), and ciprofloxacin (an inhibitor of DNA synthesis) (Giacometti et al 2005). The basis for the efficacy of these agents against biofilms of Gram-positive bacteria may be their rapid mode of action, ability to penetrate the biofilm extracellular polymeric substance (EPS) matrix (Souli and Giamarellou, 1998), or the fact that their activity is not growth rate-dependent.…”
Section: Studies Using In Vitro Model Systems: Bacterial Biofilmsmentioning
confidence: 98%